Natural Language-Based Interface Design for Early Childhood Education Applications: A Case Study of English Language Learning - Agustina, Ika; Rahman, Rashid; Fariq, Aiman (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
The design of user interfaces for early childhood education applications plays a crucial role in facilitating effective learning experiences. With the rise of digital technologies, natural language interfaces have become an essential tool, particularly in language learning applications for young children. However, there remains a gap in understanding how to design natural language interfaces that are both engaging and educational for early learners. This study focuses on the design and evaluation of a natural language-based interface for an English language learning application aimed at children aged 4 to 7. The primary objective is to explore how a conversational, child-friendly interface can enhance language acquisition while ensuring usability and engagement. The research employs a design-based approach, involving iterative prototyping and testing with a group of 30 preschool children. The interface incorporates voice recognition and conversational AI to facilitate interactive learning. User feedback and performance data were analyzed to assess usability, engagement, and learning outcomes. The results indicate that children responded positively to the natural language interface, with improved engagement and retention in language learning tasks. The intuitive design and conversational elements were found to be particularly effective in maintaining attention and enhancing comprehension. This study highlights the potential of natural language interfaces in early childhood education, demonstrating that well-designed interfaces can significantly contribute to language learning in young children.